Mutations of the RET gene in isolated and syndromic Hirschsprung's disease in human disclose major and modifier alleles at a single locus. Issue 5 (27th January 2006) - de Pontual, L; Pelet, A; Trochet, D; Jaubert, F; Espinosa-Parrilla, Y; Munnich, A; Brunet, J-F; Goridis, C; Feingold, J; Lyonnet, S; Amiel, J
Abstract : Background: In Hirschsprung's disease (HSCR), a hypomorphic allele of a major gene, RET, accounts for most isolated (non-syndromic) cases, along with other autosomal susceptibility loci under a multiplicative model. However, some syndromic forms of HSCR are monogenic entities, for which the disease causing gene is known. Objective: To determine whether RET could be considered a modifier gene for the enteric phenotype on the background of a monogenic trait. Methods: The syndromic HSCR entities studied were congenital central hypoventilation (CCHS) and Mowat-Wilson syndrome (MWS), caused by PHOX2B and ZFHX1B gene mutations, respectively. The RET locus was genotyped in 143 CCHS patients, among whom 44 had HSCR, and in 30 MWS patients, among whom 20 had HSCR. The distribution of alleles, genotypes, and haplotypes was compared within the different groups. To test the interaction in vivo, heterozygous mice were bred for a null allele of Phox2b and Ret genes. Results: RET was shown to act as a modifier gene for the HSCR phenotype in patients with CCHS but not with MWS. The intestine of double heterozygote mice was indistinguishable from their littermates. A loss of over 50% of each gene function seemed necessary in the mouse model for an enteric phenotype to occur. Conclusions: In CCHS patients, the weak predisposing haplotype of the RET gene can be regarded as a quantitative trait, being a risk factor for the HSCR phenotype, while in MWS, for which the HSCR penetrance is high, the role of the RET predisposing haplotype is not significant. It seems likely that there are both RET dependent and RET independent HSCR cases.